PENGARUH PENGETAHUAN AKUNTANSI DALAM MEMODERASI ANTARA PEMAHAMAN DAN SOSIALISASI TERHADAP KEPATUHAN PAJAK BAGI UMKM - Ripda Nur Adha; Vargo Christian L. Tobing (LPPM Universitas Putera Batam, 2026)
This study aims to analyze the effect of tax understanding and tax socialization on the tax compliance of Micro, Small, and Medium Enterprises (MSMEs), as well as the role of accounting knowledge in moderating the relationship between these variables. This research employs a quantitative method with a survey approach and a cross-sectional research design. The data used are primary data obtained through the distribution of questionnaires to MSME actors who are registered as taxpayers and operate in Batam Kota District. The sampling method used is purposive sampling with criteria that the MSMEs are actively operating and registered as taxpayers. Data analysis was conducted using multiple linear regression analysis and Moderated Regression Analysis (MRA) to examine the role of the moderating variable. All data were processed using SPSS software to ensure valid and reliable research results. The population of this study consists of all MSME actors registered as taxpayers in Batam Kota District, with a sample of 91 respondents who met the research criteria. The results indicate that tax understanding and tax socialization have an effect on MSME tax compliance, as evidenced by a t-test value of 56.331 > 3.099 and a significance level of 0.00 < 0.05. In addition, accounting knowledge is proven to be able to moderate the effect of tax understanding and tax socialization on MSME tax compliance, as indicated by a regression coefficient of 0.026 and a significance level of 0.005 < 0.05. The implications of this study are expected to provide practical contributions for MSME actors in improving tax compliance through enhancing tax understanding and accounting knowledge. For the government, particularly tax authorities, the findings of this study may serve as a reference in designing more effective tax socialization strategies. Theoretically, this study is expected to enrich the literature related to MSME tax compliance in Indonesia. Keywords : Tax Compliance; Tax Understanding; Tax Socialization; Accounting Knowledge; MSMEs.